How is 0.80 greater and 0.8 smaller please be as detailed as you can :) Stretch your thinking always gets me :)
How is 0.80 greater and 0.8 smaller please be as - 1

Answers

Answer 1
Answer: His error is that while 80 is greater than 8, 0.80 = 80/100 = 8/10 and 0.8 = 8/10, so they are equivalent. 

Related Questions

Hey guys, I need help with this
What is the solution to the system of equations represented by these two lines?HelpA.(3, 1)B.(3, 0)C.(1, 3)D.(0, 6)
X+5y=8 2x-5y=1 What is the solution?
A 1350 kg car travels at 12 m/s. What is it's kinetic energy
Each deli sandwich made uses 1/4 pound of roast beef. Marisa started with 5 pounds of roast beef and now has 3/4 pounds left.How many deli sandwiches did she make?

Here goes another question: 4/5%9/10 and please if you can with procces

Answers

When you divide a fraction by another fraction, it is the same thing as multiplying that fraction by its reciprocal.

The reciprocal is the 'flipped' version of a fraction where the numerator becomes the denominator and the denominator becomes the numerator.

for example, the reciprocal of 9/10 is 10/9

Knowing this information 4/5÷9/10 is the same as 4/5×10/9

Now we can solve...

(4)/(5) * (10)/(9) = (40)/(45) = (8)/(9)

Answer= 8/9

8/9 is the answer to your question 

A card was selected at random from a standard deck of cards. The suit of the card was recorded, and then the card was put back in the deck. The table shows the results after 40 trials.What is the relative frequency of selecting a diamond?




Outcome Club Diamond Heart Spade
Number of 8 12 11 9
trials
_________________________________________________




A.


23%


B.


25%


C.


30%


D.


42%

Answers

Relative frequency : total number of diamonds / total number of cards drawn = 11/40=0.3

The answer is 30% : C

30% is the answer to this question

-4x+3y=-2

y=x-1

y=? x=?​

Answers

Answer:

x=-1 , y=-2

Step-by-step explanation:

Replace y in the first equation with x-1.

So, we have -4x+3(x-1)=-2

Multiply brackets with 3: -4x+3x-3=-2

-4x+3x=-2+3 (-3 becomes +3 after it changes sides)

-x=1 /*(-1)

x=-1

After we have x we include it in y=x-1

y=-1-1

y=-2

Find the solutions to the equation by completing the square.x² - 6x = 7
x² - 6x___= 7
(x - ² = ___
x - 3= +/-___
x-3=__and x-3 =__

Answers

Answer:

Step-by-step explanation:

hello :

x² - 6x = 7

x² - 6x+9-9___= 7

(x - 3 )²= __16_

x - 3= +/-_4__

x-3=4__and x-3 =_-4_

Write three equivalent ratios for 18/6

Answers

There is 9/3, 3/1 and 36/12
18 ÷ 6 = 3
6 ÷ 6 = 1
Therefore, one equivalent ratio is 3/1

In order to find any other equivalent ratios, all you need to do is multiply/ divide the same number by both the numerator and the denominator.

Two more examples:  
3 X 3 = 9
1 X 3 = 3
9/3

3 X 10 = 30
1 X 10 = 10
30/10 

Rewrite this equation in the form y = ax + b.
Y-3 = 1/2x+1

Answers

Answer: y = 1/2x + 4